2011
DOI: 10.1149/1.3570279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Sulfide on Electrochemical Oxidation of Syngas for SOFC Applications

Abstract: Addition of 0.5% hydrogen sulfide into syngas improved the performance of a oxygen conducting solid oxide fuel cell by enhancing the electrochemical oxidation of carbon monoxide. However, there was no consumption of hydrogen sulfide, as determined by mass spectrometric and gas chromatographic analyzes of the effluent gases during potentioidynamic and potentiostatic runs. The anode was a composite of lanthanum strontium titanate and yttrium cerium oxide. The electrochemical performance of the fuel cell fuelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was found that La 0.4 Sr 0.6 TiO 3AEd (LST) and YDC composite was a stable, high performance material for use as anode in SOFCs fed by 0.5% H 2 S-containing syngas, whereas pure CeO 2 was not chemically stable using the same fuel. 117 Moreover, both LST and YDC were synthesized using citrate-nitrate gel combustion method. 118 The obtained LST and YDC powders were ball-milled and calcined to obtain the LST-YDC composite anode.…”
Section: Lst-based Composite Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that La 0.4 Sr 0.6 TiO 3AEd (LST) and YDC composite was a stable, high performance material for use as anode in SOFCs fed by 0.5% H 2 S-containing syngas, whereas pure CeO 2 was not chemically stable using the same fuel. 117 Moreover, both LST and YDC were synthesized using citrate-nitrate gel combustion method. 118 The obtained LST and YDC powders were ball-milled and calcined to obtain the LST-YDC composite anode.…”
Section: Lst-based Composite Anode Materialsmentioning
confidence: 99%
“…Table 3 compares the fuel cell performances of LST-based anode materials when the fuel contained trace amount of H 2 S. It is clearly shown that the performance was dramatically improved when H 2 S was present in the fuels such as 117,118 . This can also be observed clearly in Fig.…”
Section: H 2 S-induced Enhancement For Electrochemical Reaction On Ls...mentioning
confidence: 99%